Epidemiological aspects of headache in elderly patients in the Outpatient Headache Sergipe - Jesus, Alan Chester Feitosa de; Barreto, Débora Dias (Headache Medicine, 2010)
Introduction: Elderly patients constitute important parcel of all the medical care in Brazil. The headache continues being the more frequent neurological complaint in this population; its peculiarities in this age have received special attention due to presence of distinct characteristics and a biggest possibility of secondary causes. Objective: To determine the prevalence and characteristic of chronic headaches in aged patients. Material and Methods: Carried through retrospective and descriptive study in the Clinic of Chronic headache of the University Hospital of the UFS, where the variable had been studied: prevalence, age, sex, classification of the chronic headaches, comorbidities, abnormality/normality in the neurological examination and number of patients who hadreturned for a second consultation. Results: The ratio of elderly was of 5.37%. The more frequent headache was migraine(45.94%) and tensional type headache (21.62%), being that 32.43% correspond other types of chronic headaches. Conclusion: These findings suggest that the chronic headache continues being prevalent in the aged ones, being more common in women and that the type most frequent in aged continues being a primary chronic headache, the migraine, even so the secondary chronic headaches increase in frequency in this age.